Evaluation of a Current Vehicle Load Model Using Weigh-in-Motion Records: A Case in China - Xu, Zigang; Han, Qiang; Jia, Junfeng; Zhong, Zilan; Huang, Chao (The Baltic Journal of Road and Bridge Engineering, 2016)
In order to assess the vehicle load carrying capacity of existing bridges on the national highway G103 in Beijing, the vehicle load model for the practical traffic flow conditions needs to be determined. Based on the traffic axle load data measured by the weigh-in-motion system and the methods proposed by General Code for Design of Highway Bridges and Culverts (JTG D60-2004) and Code for Design of Highway Reinforced Concrete and Prestressed Concrete Bridges and Culverts (JTG D62-2004), the vehicle load parameters under practical traffic flow conditions are investigated. A typical 6-axle vehicle model with a 2-1-3 axial pattern is proposed by using the statistical analysis of total weight, axial weight, etc. The live load effects of Daliushu No. 2 Bridge, one highway bridge on the national highway G103, are analyzed using the proposed model and compared to the vehicle load model given in the Chinese code. The results show that there are great differences in the vehicle load parameters and the live load effects from the proposed vehicle load model increased by 20–50% compared with the model given by the code. The overweight vehicles are potential threats to the safety of existing bridges.